Storage stability of spray-dried papaya (Carica papaya L.) powder packaged in aluminium laminated polyethylene (ALP) and polyethylene terephthalate (PET) - Wong, C. W. (2017)
The physiochemical characteristics and microbiological study of spray-dried papaya powder kept in aluminium laminated polyethylene (ALP) and polyethylene terephthalate (PET) at accelerated storage (38 ± 2°C, 90% relative humidity (RH)) for 7 weeks were evaluated. The final water activity (Aw) of the spray-dried papaya powder did not exceed 0.6 for both packaging materials, which showed that the powder was shelf-stable. The overall adsorbed moisture of spray-dried powder was significantly (p<0.05) different for both packaging materials, whereby the moisture content of powder packaged in PET was doubled (13.28%) of those packaged in ALP (6.38%) by the end of 7 weeks storage. A larger increase of hygroscopicity was observed for powder packaged in PET (37.00%) compared to ALP (32.98%). Powder packaged in ALP had good solubility (85.19-97.14%) with storage time, while less than 80.00% solubility for powder kept in PET after 4th week of storage. The flowability of powder was significantly (p<0.05) decreased for both packaging materials upon storage. The degree of caking for powder packaged in PET was doubled (86.45%) than of 42.44% (ALP). β-carotene was degraded from an initial of 1.83 µg/g to 0.95 µg/g and 0.16µg/g for powder stored in ALP and PET, respectively. Powder packaged in ALP was microbiological safe as it had a log CFU/ml of 2.67. The results indicated that the powder packaged in ALP was with acceptable qualities and stability. Thus, ALP packaging with storage conditions of 38°C and RH 90% was better suited for keeping spray-dried papaya powder.